Comprehensive transcriptomic analysis of age-, dark-, and salt-induced senescence reveals underlying mechanisms and key regulators of leaf senescence in Zoysia japonica - Wang, Lanshuo; Doan, Phan Phuong Thao; Chuong, Nguyen Nguyen; Lee, Hyo-Yeon; Kim, Jin Hee; Kim, Jeongsik (Frontiers in Plant Science, 2023)
The lawn grass Zoysia japonica is widely cultivated for its ornamental and recreational value. However, its green period is subject to shortening, which significantly decreases the economic value of Z. japonica, especially for large cultivations. Leaf senescence is a crucial biological and developmental process that significantly influences the lifespan of plants. Moreover, manipulation of this process can improve the economic value of Z. japonica by extending its greening period. In this study, we conducted a comparative transcriptomic analysis using high-throughput RNA sequencing (RNA-seq) to investigate early senescence responses triggered by age, dark, and salt. Gene set enrichment analysis results indicated that while distinct biological processes were involved in each type of senescence response, common processes were also enriched across all senescence responses. The identification and validation of differentially expressed genes (DEGs) via RNA-seq and quantitative real-time PCR provided up- and down-regulated senescence markers for each senescence and putative senescence regulators that trigger common senescence pathways. Our findings revealed that the NAC, WRKY, bHLH, and ARF transcription factor (TF) groups are major senescence-associated TF families that may be required for the transcriptional regulation of DEGs during leaf senescence. In addition, we experimentally validated the senescence regulatory function of seven TFs including ZjNAP, ZjWRKY75, ZjARF2, ZjNAC1, ZjNAC083, ZjARF1, and ZjPIL5 using a protoplast-based senescence assay. This study provides new insight into the molecular mechanisms underlying Z. japonica leaf senescence and identifies potential genetic resources for enhancing its economic value by prolonging its green period.